Makna Simbolik dalam Al-Qur’an (Studi Komparatif Tafsir al-Azhar dan Tafsir al-Munir) - Nofri Yadi; Rusydi AM; Efendi Efendi (Dinasti Research, 2024)
Research on symbolic meaning in the Qur'an surah al-Baqarah/2: 115, al-A'raf 7:57 and al-Anfal/8: 17 is based on the belief that the Qur'an can only be understood just textually, you don't need to understand it contextually. After examining in depth the tafsir of al-Azhar and Wahbah az-Zuhaili, it was found that understanding the Qur'an is not only textual but also contextual, one of which is by understanding the symbolic meaning of the Qur'an. This research aims to reveal the symbolic meaning of the Al-Qur'an (comparative study of tafsir al-Azhar and tafsir al-Munir). To answer the question above, the researcher conducted research using a research library or literature based on reviewing tafsir books and related books, while the method used in this research was muqaran tafsir. The primary data source in this research is the Koran surah al-Baqarah/2: 115, al-A'raf 7:57 and al-Anfal/8: 17 using the tafsir al-Azhar and tafsir al-Munir. Secondary data is in the form of books, interpretations of articles and other works related to this research. The results of this research are that it can be understood in Surah al-Baqarah/2: 115 the meaning of Allah who put fear into the hearts of the Prophet's enemies, namely by conveying pasih that far away could hit them, especially when facing the Prophet at close range they would definitely be defeated by the prophet and his companions. The voice of al-A'raf 7:57 explains that the Qur'an is a source of faith that will revive the hearts of the dead and it is also with faith that the hearts of living people can understand the holy verses of the Qur'an. As for surah al-Anfal/8: 17, it can be understood that if a person faces to pray then there is his Qibla, when he does not know the direction of the Qibla for prayer or if a person does not know the direction of the Qibla then Allah will be pleased with him when he faces the Qibla. the.